2015
DOI: 10.1159/000373881
|View full text |Cite
|
Sign up to set email alerts
|

Association of Peripheral Total and Differential Leukocyte Counts with Obesity-Related Complications in Young Adults

Abstract: Objective: Obesity has been demonstrated to be associated with elevated leukocytes in adults and children. This study assessed the associations between peripheral total and differential leukocyte counts and obesity-related complications in young adults. Methods: 12 obese (median age 21.5 (range 19-28) years, median BMI 35.7 (range 32.0-44.9) kg/m2) and 11 normal (median age 23 (range 18-27) years, median BMI 19.5 (range 18.1-21.7) kg/m2) adults were enrolled. Complete blood count and seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
5
31
1
Order By: Relevance
“…Moreover, obesity has been defined as a state of chronic low-grade inflammation in which leucocytes might be involved 36. Quite a few studies have observed increased WCC among subjects with overweight or obesity7 22 37 38 suggesting that leucocytes are involved in the development of obesity-related comorbidities. Stratified analysis by smoking status and joint effect analysis by smoking and BMI status showed apparent evidence for effect modification by smoking and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, obesity has been defined as a state of chronic low-grade inflammation in which leucocytes might be involved 36. Quite a few studies have observed increased WCC among subjects with overweight or obesity7 22 37 38 suggesting that leucocytes are involved in the development of obesity-related comorbidities. Stratified analysis by smoking status and joint effect analysis by smoking and BMI status showed apparent evidence for effect modification by smoking and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte numbers increase with obesity, both in the circulation and in local adipose tissue depots, and are correlated with such proinflammatory diseases as type 2 DM (42) and liver steatosis (43). Our flow cytometry and immunohistochemistry data indicate that the frequency of hematopoietic cells was significantly higher in the synovium than in the IPFP from lean patients with OA, with a further increase in the number of CD451 cells being seen in those with obesity, suggesting a more proinflammatory profile of both tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin resistance appears to be associated with low-grade chronic inflammation, originating from adipose tissue [1,2]. Obesity-associated chronic inflammation is characterized by an immense infiltration of macrophages in the adipose tissue [1] with secretion of pro-inflammatory cytokines, such as interleukin 6 (IL-6) [2,3], and of peripheral leukocytosis [4,5]. …”
Section: Introductionmentioning
confidence: 99%